Comparative Microstrain Study of Internal Hexagon and Plateau Design of Short Implants Under Vertical Loading - Nishioka, Renato Sussumu [UNESP]; Rodrigues, Vinicius Aneas [UNESP]; De Santis, Leandro Ruivo [UNESP]; De Melo Nishioka, Gabriela Nogueira [UNESP]; Miyazaki Santos, Vivian Mayumi [UNESP]; Souza, Francisley Avila [UNESP] (Lippincott Williams & Wilkins, 2016)
Purpose: To quantify microstrain development during axial loading using strain gauge analysis for short implants, varying the type of fixture-abutment joint and thread design. Materials and Methods: An internal hexagon implant (4 x 8 mm) and a plateau design implant (4 x 8 mm) were embedded on the center of 10 polyurethane blocks with dimensions of 190 x 30 x 12 mm. The respective abutments were screwed onto the implants. Four strain gauges (SGs) were bonded onto the surface of each block, and 4 vertical SGs were bonded onto the side of each block. Axial load of 30 kgf was applied for 10 seconds in the center of each implant. Results: The data were analyzed statistically by analysis of variance for repeated measures and Tukey test (P > 0.05). The interaction between implant and region factors have been statistically significant (P = 0.0259). Tukey test revealed a difference on plateau's horizontal region. The cervical region presented higher microstrain values, when compared with the medium and apical regions of the implants. Conclusion: Within the purpose of the study, the type of fixture-abutment joint is a relevant factor to affect the amount of stress/strain in bone simulation. The microstrain development was concentrated on the cervical region of the implant.
Keywords: dental prosthesis; dental implant-abutment design; dental implants